Implementation of the Curfew as a Policy of the Aceh Government on Handling COVID-19: A Social Responsibility - Khalida Ulfa; Safirussalim Safirussalim (Department of Government Studies, Universitas Syiah Kuala, 2021)
The world was shocked by an outbreak in East Asian countries, precisely in China, Wuhan, Hubei Province, last December 2019. This outbreak is known as Coronavirus 2019 (COVID-19), which attacks the respiratory tract and leads to death. This COVID-19 has hit worldwide, including Indonesia and has spread to all provinces, including the province of Aceh. The Aceh government has imposed restrictions on activities at night to break the chain of the spread of COVID-19. However, polemics have emerged from the community about this policy. The purpose of writing this article is to analyze the implementation of the Curfew as a policy of the Aceh government towards dealing with COVID-19 and the obstacles to its implementation. The research method uses a qualitative descriptive approach. The data sources are obtained from journals and the latest news about COVID-19—the data analysis technique used Nvivo plus 12 analysis. The results showed that the curfew policy in Aceh could not be fully implemented properly due to the pros and cons of the community, even though the government had taken its social responsibility in society. Thus, the policy must be thoroughly considered for the sake of the survival and welfare of the community, especially for those from the lower-middle economic class.